Studies on steel fibre reinforced light weight aggregate concrete subjected to cold ocean environment - Muste, Traian Gheorghe (1988)
Thesis (M.Eng.)--Memorial University of Newfoundland, 1989. Engineering and Applied Science Bibliography: leaves 258-269. The present research, triggered by the potential development of offshore oil exploitation off Newfoundland coast, concludes a part of a research programme, at Memorial University, St. John's, Nfld, Canada, in which the use of lightweight aggregate concrete (LAC) and steel fibres reinforced lightweight aggregate concrete (SFRLAC) as structural materials for potential Arcticand sub-Arctic structures was investigated. The work was financed from NSERC Grant # 3117 6. -- The thesis starts with the literature review and introduction in Chapter 1, and consists of two main parts. The first one, Chapters 2 and 3, presents a few relevant rheological and hardened state properties of lightweight aggregate concrete (LAC) and steel fibre reinforced lightweight aggregate concrete (SFRLAC); also in Chapter 2, the composition of concrete was determined to meet the specifications, and steel fibres were added by a trial-and-error method to obtain the most suitable SFRLAC. The second part, Chapters 4 to 6, includes the results of the theoretical and experimental analysis of the behaviour of the LAC and SFRLAC plates subjected to static loading. In Chapter 4, the design of the plates, based on the available semi-empirical methods is presented; in addition, a finite element computer code used in this work is introduced, and its predictions are compared with the experimental results in Chapter 6. The laboratory experimental work is presented in Chapters 2, 3, 5 and 6. -- The behaviour of the plates with regard to deformation, strain, cracking pattern, ultimate capacity, and modes of failure 5 is given in Chapter 6; the effect of varying the shear and flexural reinforcement on the behaviour of the plates was also investigated. The comparison of theoretical predictions, as described in Chapter 4, using the actual properties of the concrete and reinforcement, with the experimental results is also given. Throughout the thesis, one main purpose was to assess the suitability of the LAC and SFRLAC to cold ocean environment (COE), simulated under laboratory conditions. Another main purpose of the work was to assess the shear capacity of the plates, and to improve it. The shear capacity is calculated, as presented in Chapters 4 and 6, according to conventional and modified conventional reinforced concrete theory. The fibres contribution to the behaviour of the plates was also investigated. It is concluded in Chapter 7, that LAC, and especially SFRLAC, are suitable structural materials for Arctic and sub-Arctic offshore structures, possessing suitable structural behaviour.